It is not their war: the impact of military operations on Philippine migrant care workers for elderly people in Israel - Ron P (Dove Medical Press, 2015)
Pnina Ron School of Social Work, Faculty of Welfare and Health Sciences, University of Haifa, Haifa, Israel Objective: A majority of work immigrants from the Philippines came to Israel to fill positions involving personal and nursing care. Most of them were in Israel during the Second Lebanon War, the Cast Lead operation, and the Protective Edge Operation. These migrant care workers experienced these events no differently than did the Israeli population. The goal of this study was to examine the connections between the Philippine migrant care workers’ exposure to the military operations and the levels of post-traumatic stress disorder (PTSD), death anxiety, and burnout among them.Methods: A random sample of 147 Philippine migrant care workers was recruited through four agencies that employ migrant care workers. Participants completed a self-report questionnaire.Results: Philippine migrant care workers reported high levels of PTSD, high levels of death anxiety, and low levels of burnout. Levels of exposure were positively associated with levels of PTSD, death anxiety, and negatively with burnout. A significant inverse relationship was found between interpersonal variables (self-esteem and sense of mastery) and the PTSD, death anxiety, and burnout levels reported by the participants. Keywords: elderly care, death anxiety, work immigrants, burnout, military operations